Prognostic relevance and performance characteristics of serum IGFBP‐2 and PAPP‐A in women with breast cancer: a long‐term Danish cohort study. (3rd May 2018) - Espelund, Ulrick; Renehan, Andrew G.; Cold, Søren; Oxvig, Claus; Lancashire, Lee; Su, Zhenqiang; Flyvbjerg, Allan; Frystyk, Jan
Abstract: Measurement of circulating insulin‐like growth factors (IGFs), in particular IGF‐binding protein (IGFBP)‐2, at the time of diagnosis, is independently prognostic in many cancers, but its clinical performance against other routinely determined prognosticators has not been examined. We measured IGF‐I, IGF‐II, pro‐IGF‐II, IGF bioactivity, IGFBP‐2, ‐3, and pregnancy‐associated plasma protein A (PAPP‐A), an IGFBP regulator, in baseline samples of 301 women with breast cancer treated on four protocols (Odense, Denmark: 1993–1998). We evaluated performance characteristics (expressed as area under the curve, AUC) using Cox regression models to derive hazard ratios (HR) with 95% confidence intervals (CIs) for 10‐year recurrence‐free survival (RFS) and overall survival (OS), and compared those against the clinically used Nottingham Prognostic Index (NPI). We measured the same biomarkers in 531 noncancer individuals to assess multidimensional relationships (MDR), and evaluated additional prognostic models using survival artificial neural network (SANN) and survival support vector machines (SSVM), as these enhance capture of MDRs. For RFS, increasing concentrations of circulating IGFBP‐2 and PAPP‐A were independently prognostic [HRbiomarker doubling : 1.474 (95% CIs: 1.160, 1.875, P  = 0.002) and 1.952 (95% CIs: 1.364, 2.792, P  < 0.001), respectively]. The AUCRFS for NPI was 0.626 (Cox model), improving to 0.694 ( P  = 0.012) with the addition of IGFBP‐2 plus PAPP‐A. Derived AUCRFS using SANN and SSVM did not perform superiorly. Similar patterns were observed for OS. These findings illustrate an important principle in biomarker qualification—measured circulating biomarkers may demonstrate independent prognostication, but this does not necessarily translate into substantial improvement in clinical performance. Abstract : We measured a set of IGF biomarkers, including IGFBP‐2 and PAPP‐A in a well‐characterized cohort of Danish women with breast cancer undergoing primary surgery and adjuvant therapies. We showed that increasing concentrations of circulating IGFBP‐2 and PAPP‐A were independently prognostic, but the addition of these biomarkers to models including NPI only modestly improved performance. We could have readily reported the prognostic significance of IGFBP‐2 and PAPP‐A, and speculated on its clinical utility—but instead, we directly tested the addition of these biomarkers to already‐used prognostic scores in the clinic.